Bioecological characteristics of mangrove snail in Langsa mangrove forest, Aceh, Indonesia: Diversity and community structure - Mardiah, Nur Ainun; Erlangga, Erlangga; Syahrial, Syahrial; Hadinata, Fitra Wira; Ezraneti, Riri; Barat, Welmar Olfan Basten; Leni, Yusyam (Journal of Marine Studies, 2024)
The most crucial aspect of managing an ecosystem or habitat is knowledge about accompanying biota, such as snails. The research on mangrove snails in the KPH Region III Aceh City of Langsa area was conducted in November 2021 with the goal of evaluating species diversity, density, ecological index, distribution, and their link to surrounding environmental conditions. Snail data was obtained via quadrat transects, with observation stations established using purposive sampling.The snail diversity was found to be five species from four families, with the highest density found in N. planospira (03.13 ind/m2). The diversity index was low (H' ‰¤ 2.0), dominance was moderate (0.5 < C ‰¤ 0.75), and uniformity tended to be balanced (0.5 < E ‰¤ 0.75). The distribution pattern is clustered (IÎ´> 1), with C. cingulata being abundant (83.33%), and C. capucinus being frequently found (50.00%), N. planospiraonly found occasionally (36.11%), and L. scabra and T. telescopium are relatively uncommon (11.11% and 0.56%, respectively), with a link to environmental variables indicating that T. telescopium prefers fine mud substrates. Meanwhile, C. cingulata, C. capucinus, L. scabra, and N. planospiralive in habitats with fine mud substrates that are more solid than T. telescopiums habitats.